Penentuan alternatif pendukung keberhasilan peningkatan produksi dan daya saing kakao menggunakan analytical hierarchy process (AHP) - Devi Maulida Rahmah; Kania Fitrah Maulida; Januardi Januardi (AGROINTEK, 2026)
Amidst the increasing consumption of cocoa and its derivative products, Indonesia has become the 7th largest cocoa producer in the world. Most of the cocoa produced by Indonesia is exported abroad, with the main export destinations being Malaysia, Vietnam, the United States, India, China, the Netherlands, and Australia. However, Indonesia is currently experiencing a decline in productivity and competitiveness caused by declining production and poor cocoa bean yields. This causes the amount of cocoa to not meet the demands of processors so that processors import cocoa beans. Therefore, it is necessary to know the solution to increase cocoa productivity and competitiveness in Indonesia. AHP is used in determining decisions that can encourage increased cocoa production and competitiveness in Indonesia involving 5 stakeholders. The results of the study showed that the best solution that can be done to increase cocoa production and competitiveness in West Java is to improve the quality of production and cocoa beans, through farmer guidance on Good Agriculture Practices and Good Manufacturing Practices with the highest weight, namely 0.2556.